Constituting the Violence of Criminalized Women - Comack, Elizabeth (Canadian journal of criminology and criminal justice, 2007)
Recent efforts to make sense of the Violent Woman have revolved around three different (yet not disconnected) constructs: "victim," "mad," and "bad." One issue that has been missing in discussions of the Violent Woman, however, is how women who use violence constitute themselves. In this study, using in-depth interviews with 18 criminalized women, we aim to uncover the women's own discursive constructions and the discourses they draw from in their efforts at framing identity. How and where is violence situated in the women's accounts of their lives? How do the women constitute themselves? What discourses do they draw from (and resist)? Do the prevailing constructs of the Violent Woman as "victim," "mad," or "bad" have resonance for these women? In the process, we argue that each of these constructs, while having some resonance in the women's accounts, fails to capture the complexity of their lives. Because identity is fractured and multiple, violence in the lives of criminalized women (their own violence and that which is directed at them) cannot be rendered plausible by imposing a master status template. We conclude by considering the implications of this analysis for making sense of women's violence. [ABSTRACT FROM AUTHOR]